2008
DOI: 10.1097/hjr.0b013e328305deef
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of double product reserve

Abstract: In this study population, DP reserve had greater prognostic power than metabolic equivalents, maximal HR or systolic blood pressure, or HR recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 25 publications
3
14
0
1
Order By: Relevance
“…Bouzas-Mosquera et al [20] demonstrated Mark Whitman et al, Downstream cardiac testing following a negative exercise stress test that a substantial increase in SBP alone during exercise testing was associated with a significantly lower risk of mortality and CV events. Individuals achieving greater increases in RPP during exercise have also been shown to have less CV events over time in both those with, and without significant CAD [4,5,21]. The current study confirms this finding, where a significant difference in CV-related events was observed between the two groups from 2 years follow up (p < 0.05; Fig.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Bouzas-Mosquera et al [20] demonstrated Mark Whitman et al, Downstream cardiac testing following a negative exercise stress test that a substantial increase in SBP alone during exercise testing was associated with a significantly lower risk of mortality and CV events. Individuals achieving greater increases in RPP during exercise have also been shown to have less CV events over time in both those with, and without significant CAD [4,5,21]. The current study confirms this finding, where a significant difference in CV-related events was observed between the two groups from 2 years follow up (p < 0.05; Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Normal values for RPP have been proposed for clinical and nonclinical populations at rest and at maximal exercise [1][2][3]. During EST, RPP has been extensively investigated as a prognostic variable [4][5][6][7]. In a retrospective cohort study of 1759 men, rate pressure product reserve (RPPR) (the difference between RPP at rest and maximal exercise) was the strongest predictor of 7-year cardiovascular (CV) status, even after adjustment for age, beta-blocker use and Duke Treadmill Score [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood pressure was then averaged into hourly blood pressures. As a surrogate measure of myocardial oxygen consumption, 16 the RPP was calculated from the mean hourly HRs and the mean hourly systolic blood pressures: RPP = HR × SBP.…”
Section: Animals Materials and Methodsmentioning
confidence: 99%
“…In critically ill patients, many CCR-related parameters (oxygen consumption, stroke work, cardiac power …) have been studied, most of which are derived from cardiac index (CI) magnitude during a dobutamine test [6]. Double product (systolic arterial pressure × heart rate) is an old hemodynamic tool, closely related to CR and known to have low values in chronic heart failure [79]. Its evolutive pattern has never been established during shock states.…”
Section: Introductionmentioning
confidence: 99%